The making of memory in the Middle Ages
1 online resource.
Keywords: Memory in the Middle Ages has received particular attention in recent decades; yet; the topic remains difficult to grasp and the research on it rather fragmented. This book gathers particular case studies on memory in different parts of medieval Europe and in a variety of fields including literatures, languages, manuscript studies, history, history of ideas, philosophy, social history and art history. The studies address, on the one hand, memory as means of storing and recuperating knowledge (arts of memory and memory aids), and, on the other hand, memory as remembering and constructing the past (including the subject of forgetting). It should be useful to all interested in medieval culture, literature and history. Contributors are Milena Bartlová, Bergsveinn Birgisson, Irene Bueno, Vincent Challet, Greti Dinkova-Bruun, Lucie Doležalová, Dávid Falvay, Carmen Florea, Cédric Giraud, Laura Iseppi de Filippis, Farkas Gábor Kiss, Rüdiger Lorenz, Else Mundal, Előd Nemerkényi, William J. Purkis, Slavica Ranković, Lucia Raspe, Kimberly Rivers, Victoria Smirnova, Francesco Stella, Péter Tóth, Tamás Visi, Jon Whitman and Rafał Wójcik.